Literature Watch Implications for transplantation. Issue 9 (29th August 2013) - Wells, Andrew D.; Bromberg, Jonathan S.
<x xml:space="preserve">Abstract</x> Donor‐specific tolerance is influenced by specialized T lymphocytes called regulatory T cells. Understanding their epigenetic regulation and other issues determining the stability of these cells may offer powerful new ways to promote their function and tolerance in organ transplant recipients.